Pelatihan Integrasi Model Pembelajaran dalam Learning Management System (LMS) berbasis Project untuk Meningkatan Kompetensi Pedagogi Guru Sekolah Dasar - Idam Ragil Widianto Atmojo; Matsuri Matsuri; Chumdari Chumdari; Fadhil Purnama Adi; Roy Ardiansyah; Dwi Yuniasih Saputri (Jurnal Pengabdian UNDIKMA, 2023)
The purpose of this community service activity is to improve teacher pedagogical competence in integrating learning models in a Learning Management System (LMS)-based project in ICT-based elementary schools. The method for implementing the community service activity uses training which includes the stages namely 1) Conducting Competency Analysis, 2) Conducting Student Characteristics Analysis, 3) Constructing material that is in accordance with student characteristics but still on the essence, 4) Compiling LMS, 5) Implementing the developed digital LMS. The number of participants in this community service activity were 15 elementary school teachers of SD ICT Al-Abidin and 15 teachers of SD Ta'mirul Islam in Surakarta City. The evaluation instruments used were pre-test and post-test which were analyzed descriptively. The result of this service activity is a training on integration of learning models in Learning Management System (LMS)-based projects that can improve teacher pedagogical competence. This was shown by more than 80% of the participants, namely teachers who were able to understand knowledge about the concept of Learning Management System, learning models, TPACK, integration of learning models. The positive response was shown by the teachers who looked enthusiastic and active in discussing and designing learning models that were integrated into the Learning Management System.